Pilot study evaluating frailty-focused care for hospitalised patients with chronic obstructive pulmonary disease - Tim Benson; Alan J Forster; Melanie Chin; Nha Voduc; Sunita Mulpuru; Smita Pakhale; Caroline Tessier; Julia Shaw; Julie Lawson; Delvina Hasimja; Jacqueline Sandoz; Jiro Inoue; et al. (BMJ Open Quality)
Background Frailty is associated with morbidity and mortality among people with chronic obstructive pulmonary disease (COPD), yet there are no established care pathways to manage frail patients with COPD. To address this gap, we developed, implemented and assessed the feasibility of a new frailty-focused care model for patients hospitalised with exacerbations of COPD.Methods We conducted a prospective cohort study among hospitalised patients with acute exacerbations of COPD in an academic hospital in Canada over 18 months. We developed and implemented a frailty-focused care model using the degree of frailty to guide personalised assessments, education, and care interventions during and after hospital discharge. We assessed the feasibility of using frailty-focused care in a real-world setting with prespecified targets for recruitment rate, care model completion and collection of patient-reported outcomes including symptom burden, health confidence, health status and self-management scores. Patients were followed up at 3 months after hospitalisation to reassess patient-reported outcomes.Results 87 patients used the frailty-focused care model during hospitalisation, 58 consented to participate in this study and 45 (78%) completed 3-month postdischarge follow-up. 47% (n=21) were at least mildly frail at baseline, with 35% (n=20) at risk of frailty. Target recruitment of 50 patients was achieved, and all participants completed core elements of frailty-focused care, including frailty assessment, personalised education and discharge planning. Patient-reported outcomes were measured in all participants in hospital, and in 78% (n=45) patients at 3-month follow-up. 23% (n=13) of patients initially reported feeling confident to manage their health condition. This improved to 62% (n=28) at 3-month follow-up.Conclusions This study provides a foundation to build innovative care models for frail individuals with COPD and shows it is feasible to use frailty-focused care in a real-world hospital setting. Future work requires strong patient engagement to better align frailty-focused care with patient-centred goals.